Laptop price prediction using decision tree algorithm / Nurnazifah Abd Mokti - Abd Mokti, Nurnazifah (2024)
This research project focuses on developing a laptop price prediction model using the decision tree algorithm based on laptop specifications. The objective is to provide a reliable tool for students, laptop buyers, and sellers to estimate laptop prices accurately. The project involves data collection, data preparation, and the implementation of the decision tree algorithm for price prediction. The decision tree's effectiveness and accuracy in predicting laptop prices are evaluated through rigorous testing and validation. The findings of this research aim to offer valuable insights into the relationship between laptop specifications and their corresponding prices, helpingusers make informed decisions in the laptop market. The model's interpretability and ease of use contribute to its practical applicability. The project's results and their implications are documented in a comprehensive report, providing a clear overview of the methodology, evaluation process, and potential real-world applications. Overall, this laptop price prediction model demonstrates the effectiveness of the decision tree algorithm in delivering accurate and valuable predictions for various stakeholders in the laptop industry.